Developing Arabic Multi-Dimensional Scale for Detecting Autism - Al- quryouti, Ibrahim; Ababneh, Imad (Jordan Journal of Educational Sciences, 2006)
The aim of the study was to develop an Arabic multidimensional scale to detect autism.. After auditing the items pool (68) which are the preliminary version of the scale, the researchers administered the scale to a sample of (391) children from different Arab countries. The software (SPSS) was used to analyze the collected data, and the findings were as follows: 1. The scale showed that the factorial and discriminate validity were significant. The dimensions which extracted accounted (59.11%) of the total variance; moreover, the discriminate analysis showed that the scale has the power to classify more than (77.2%) of the cases correctly. 2. The Reliability coefficient calculated by Cronbach Alpha was (0.89), whereas reliability coefficients for the dimensions of the scale ranged between (0.42 and 0.89). 3. The t-test showed that the differences between performance means of autistics and Normal children were statistically significant. The researchers recommended further studies to ensure stability, and utilizing the scale for detecting autism cases